BCG OSTEITIS - Kh. Daneshjou; M. Farzan; M.R. Giti A. Zamani (Acta Medica Iranica, 2004)
The only available vaccine against tuberculosis is BCG which has been found to protect children against disseminated tuberculosis and tuberculous meningitis. BCG is one of the safest vaccines being used, and osteitis is a rare complication of it. During a period of eight years, we had eleven cases of osteitis occuring in infants following BCG vaccination. Eight cases were female. Defect in immune response was not found in any of the patients and all got cured with simple curretage of the lesion and appropriate drug therapy without any sequelae.